Effect of Organic Manure, Biofertilizer, Phosphourus and Nitrogen on Growth, Seed Yield, Seed Quality Attributes of Green Gram (Vigna radiata L.) - DEEPAK RAO; CP SACHAN; VISHLAVATH RAMVILAS PASHWAN; ASHWINI VIJAY SAKPAL (Seed Research, 2026)
An experiment entitled “Effect of organic Manure, Bio fertilizer, Phosphorus and Nitrogen on growth seed yield and seed quality attributes of green gram” was carried out at Nawabganj farm in the Chandhra Shekhar Azad University of Agriculture and Technology, Kanpur Uttar Pradesh during the year 2018- 2019. The experiment was laid out in Randomized Complete Block Design with a five factor having Five treatments replicated three times. Organic Manure (FYM and vermicompost), bio fertilizer (PSB), Phosphorus and Nitrogen was subjected to all plots except control. Data were recorded on different parameters such as primary branches, secondary branches, DAS 50% flowering, Number of seeds per plant, Number of pods per plant, Length of pods, seed yield and Test weight of green gram, after a month laboratory observation like germination percentage, root length, shoot length, Tetrazolium test, Brick Gravel test, Electrical Conductivity, Seed Vigour Index –I and Seed Vigour Index –II were reported . The statistical analysis of the data showed that organic Manure (FYM) significantly affected all the studied attributes. The highest number Primary branches, secondary branches and DAS of 50 % flowering Number of seeds per plant, Number of seeds per plant, Number of pods per plant, pod length seed yield and Test weight were recorded highest in treatment T1 (FYM @7.5t/750 m2) followed T5 (Nitrogen @ 1.5 kg/750 m2), T4 (Phosphorus @ 3 kg/ 750 m2), T3 (PSB @ 20 gm Per Kg of seeds), T2 (Vermicompost @ 2.5t/750 m2). In Laboratory observation the highest germination percentage, root length, shoot length, Tetrazolium test, Brick Gravel test, Electrical Conductivity, Seed Vigour Index –I and Seed Vigour Index –II were recorded in treatment T1 (FYM @7.5t/750 m2) followed T5 (Nitrogen @ 1.5 kg/750 m2), T4 (Phosphorus @ 3 kg/ 750 m2), T3 (PSB @ 20 gm Per Kg of seeds), T2 (Vermicompost @ 2.5t/750 m2). In general, applications of phosphorus, nitrogen, organic and inorganic in combinations were found effective in enhancing yield in this crop.